Rasio Cycle Threshold (CT) Internal Control (IC)/CT Gen N Sars-Cov-2 dan Ekspresi Gen N Sars-Cov-2 Berhubungan dengan Tingkat Keparahan Pasien Covid-19 - Gibran Bramasta Dirgavansya; Umar Islami; Lelly Yuniarti (Bandung Conference Series: Medical Science, 2022)
Abstract. Introduction: COVID-19 is a disease caused by a virus called SARS-CoV-2, COVID-19 cases in Indonesia reached 4.2 million in October 2021. The standard for diagnosis of COVID-19 is RT-PCR because of its high specificity and sensitivity, RT -PCR produces a CT value that can describe the amount of nucleic acid and viral load of SARS-CoV-2. This study aims to analyze the relationship between the expression of SARS-CoV-2 gene N and the ratio of CT internal control/CT gene N SARS-CoV-2 with the severity of illness in COVID-19 patients. Methods: This study was an observational study with a cross-sectional approach to inpatients at Cideres Majalengka Hospital, the data was taken in the form of medical records and the results of the RT-PCR examination were CT values. The expression of the SARS-CoV-2 N gene was calculated using the saliva formula (Formula 2-ΔΔCT), while the ratio was obtained by comparing the CT values internal control /CT gene N SARS-CoV-2. The relationship of gene expression and CT ratio with severity was analyzed using the correlation test Spearman at a 95% confidence level. Results: The correlation test Spearman showed a relationship between the expression of SARS-CoV-2 Gene N (r=0.31; p=0.015) and the ratio of CT internal control/CT gene N SARS-CoV-2 (r= 0.28; p = 0.03) with the severity of COVID-19 patients. Severity is classified according to the COVID-19 Management Guidelines into mild, moderate, severe, critical. Conclusion: The conclusion of this study is that there is a relationship between the expression of SARS-CoV-2 gene N and the ratio of CT internal control/CT gene N SARS-CoV-2 with the severity of COVID-19 patients, the greater the gene expression ratio value, the severity of the patient Heavier. The ratio of CT internal control /CT gene N SARS-CoV-2 and high gene expression indicate a high viral load that can increase the severity of the patient. Abstrak. Pendahuluan: COVID-19 adalah penyakit yang diakibatkan oleh virus bernama SARS-CoV-2, kasus COVID-19 di Indonesia mencapai 4,2 juta pada Oktober 2021. Standar baku diagnosis COVID-19 adalah RT-PCR karena spesifisitas dan sensitivitasnya tinggi, RT-PCR menghasilkan CT value yang dapat menggambarkan jumlah asam nukleat dan viral load SARS-CoV-2. Penelitian ini bertujuan menganalisis hubungan ekspresi gen N SARS-CoV-2 dan rasio CT internal control/CT gen N SARS-CoV-2 dengan tingkat keparahan penyakit pasien COVID-19. Metode: Penelitian ini merupakan penelitian observasional dengan pendekatan potong lintang pada pasien rawat inap RSUD Cideres Majalengka, data diambil berupa rekam medik dan hasil pemeriksaan RT-PCR berupa CT value. Ekspresi gen N SARS-CoV-2 dihitung menggunakan rumus Livak (Rumus 2-ΔΔCT), sementara rasio didapatkan dengan membandingkan nilai CT internal control/CT gen N SARS-CoV-2. Hubungan dari ekspresi gen dan rasio CT dengan tingkat keparahan dianalisa dengan menggunakan uji korelasi spearman pada tingkat kepercayaan 95%. Hasil: Uji korelasi spearman menunjukkan adanya hubungan antara ekspresi gen N SARS-CoV-2 (r=0,31; p=0,015) dan rasio CT internal control/CT gen N SARS-CoV-2 (r= 0,28; p=0,03) dengan tingkat keparahan pasien COVID-19. Tingkat keparahan diklasifikasikan berdasar Pedoman Tatalaksana COVID-19 menjadi ringan, sedang, berat, kritis. Kesimpulan: Kesimpulan dari penelitian ini adalah terdapat hubungan antara ekspresi gen N SARS-CoV-2 dan rasio CT internal control/CT gen N SARS-CoV-2 dengan tingkat keparahan pasien COVID-19, semakin besar nilai ekspresi gen rasio maka tingkat keparahan pasien semakin berat. Rasio CT internal control/CT gen N SARS-CoV-2 dan ekspresi gen yang tinggi menunjukkan viral load yang tinggi sehingga dapat meningkatkan tingkat keparahan pasien.